SMRT sequencing and ddPCR reveal the complexity of developmental trajectories and temporal dynamics of gut bifidobacterial communities in infants - Xu Gao; Tao Zhang; Xiaoye Bai; Qiannan Wen; Dongyu Li; Lai-Yu Kwok; Heping Zhang; Zhihong Sun (Food Science and Human Wellness)
Infant intestinal microbiome is closely linked with health and risk of disease. Bifidobacterium are important components of the infant gut and are known to confer various health effects on the host. However, few studies have described the precise composition and dynamics of early infant gut bifidobacterial communities. Thus, this was a pilot study aiming to describe the developmental trajectories and temporal dynamics of bifidobacterial communities in infants before 6 months of age. A total of 28 fecal samples from 4 infants (GF, ZZ, QM, TN, respectively) were collected and analyzed after 5, 15, 30, 60, 90, 120, 150, and 180 days of birth by a bifidobacteria-target method (based on single-molecule real-time sequencing of partial bifidobacterial rpsK genes) in conjunction with droplet digital polymerase chain reaction (ddPCR). The infant fecal microbiota comprised a total of 11 bifidobacterial species, including 4 major species, i.e., B. dentium (37.35 %), B. catenulatum (32.04 %), B. breve (22.24 %), and B. animalis (8.02 %). The infant microbiota showed highly individualized developmental trajectories. The leading species for GF was B. catenulatum, with a relatively stable developmental trajectory. In ZZ, B. breve was enriched, and the developmental trajectory was rather fluctuating. The most abundant species for QM and TN was B. dentium. The developmental trajectory of B. dentium in QM showed a trend of gradual decrease, whereas an opposite trend was seen in samples of TN. The results of ddPCR confirmed large variations in quantities of bifidobacteria between infants and suggested discordances in temporal dynamics of bifidobacterial communities during the first half year of infancy. In conclusion, our results suggested that the early infant gut bifidobacterial microbiota was highly complex and temporal dynamics, with individualized developmental trajectories, which should be considered in future research of infant gut microbiota.